Prevalence of Left Ventricular Dyssynchrony in Patients with Congenital Atrioventricular Block and Long‐Term Pacing: A Three‐Dimensional Echocardiographic Study. Issue 9 (14th January 2015) - Guerra, Vitor Coimbra; de Menezes Martins, Luciana; Oliveira, Roberto Marcio; da Silva, Kátia Regina; Binotto, Maria Angelica; Tsutsui, Jeane M.; Kallil, Roberto; Costa, Roberto; Mathias, Wilson
<x xml:space="preserve">Abstract</x> Background Left ventricular (LV) dysfunction is the major reason for poor outcomes in patients with congenital complete atrioventricular block (CCAVB) and pacemaker. Long‐term pacing has been associated with LV mechanical dyssynchrony. However, the relationship of dyssynchrony and LV dysfunction is not clear. Objective We sought to evaluate the prevalence of LV dyssynchrony by real time three‐dimensional echocardiography (RT3DE) in patients with CCAVB and its association with LV dysfunction. In addition, we evaluated the agreement between RT3DE and tissue Doppler imaging (TDI) for detecting LV dyssynchrony. Method We studied 50 patients [median age 20 years old (5 months to 62 years), 68% women] with CCAVB and pacemaker who underwent complete two‐dimensional echocardiography and RT3DE. LV dyssynchrony was considered if the systolic dyssynchrony index (SDI) was ≥5%. Intraventricular mechanical delay was defined by TDI when differences in electromechanical activation between LV walls were >65 msec. Results LV systolic dysfunction was present in 16 patients (32%) by two‐dimensional and in 20 patients (40%) by RT3DE. There was a good correlation between LV ejection fraction by two‐dimensional and RT3DE (r = 0.75; P < 0.001). Fourteen (28%) patients had intraventricular dyssynchrony by TDI, while 12 (24%) had intraventricular dyssynchrony by RT3DE. There was a good agreement between LV dyssynchrony by TDI and RT3DE (Kappa=0.735; P < 0.001). There was a negative correlation between LV ejection fraction and SDI obtained by RT3DE (r = −0.58; P < 0.001) Conclusions In patients with CCAVB and long‐term pacing, LV dyssynchrony occurred in one‐third of patients and was related to LV dysfunction. There was a good correlation between dyssynchrony obtained by RT3DE and TDI.